Privatization of Singapore telecom : process and effects. - Goh, Guek Eng. (2013)
The purpose of this Applied Research Project was to do a detailed analysis of the privatization of Singapore Telecom. This research covers the seven years span, beginning in 1989 when the Government first announced its intention to privatize Singapore Telecom until 1995, which is about two years after Singapore Telecom’s privatization in 1993.